“La vraie langue française [n'] existe plus”: français parlé et pratiques multilingues comme stratégies identitaires dans le rap montréalais - Sarkar, Mela (Grenzgänge, 2006)

«Ousqu’on chill à soir?» Pratiques multilingues comme stratégies identitaires dans la communauté hip-hop montréalaise - Sarkar, Mela (Diversité urbaine, 2008)

Multilingual Codeswitching in Quebec Rap: Poetry, Pragmatics and Performativity - Sarkar, Mela; Winer, Lise (International Journal of Multilingualism, 2006)

Hybrid Identities in Quebec Hip-Hop: Language, Territory, and Ethnicity in the Mix - Sarkar, Mela; Allen, Dawn (Journal of Language, Identity & Education, 2007)
Montreal is the metropolitan hub of the province of Quebec, a French-speaking island in officially bilingual, but de facto majority English-speaking, Canada. The current youth generation represents a variety of ethnolinguistic backgrounds—French and English Canadian, but also many different immigrant-origin groups, including large Haitian and Hispanophone populations. Young adults and adolescents share French as a common language through schooling. In Quebec, hip-hop, a privileged literary–artistic and political medium for this generation, not only reflects its multilingual, multiethnic base, but also constitutes an active and dynamic site for the development of an oppositional community that encourages the formation of new, hybrid identities for youth. The authors draw on interviews with rappers of Haitian, Dominican, and African origin, and analysis of lyrics by these MCs, to highlight ways in which the discourses of “conscious” Quebec hip-hop promotes particular ideologies and identities in a context of migration/resettlement and globalization of youth culture.
Publisher: Routledge _eprint: https://doi.org/10.1080/15348450701341253
Keywords: Quebec; hip-hop; identity; multilingual; rap; youth culture

‘Ch'us mon propre Bescherelle’: Challenges from the Hip-Hop nation to the Quebec nation - Low, Bronwen; Sarkar, Mela; Winer, Lise (Journal of Sociolinguistics, 2009)
We examine the uses of and attitudes towards language of members of the Montreal Hip-Hop community in relation to Quebec language-in-education policies. These policies, implemented in the 1970s, have ensured that French has become the common public language of an ethnically diverse young adult population in Montreal. We argue, using Blommaert's (2005) model of orders of indexicality, that the dominant language hierarchy orders established by government policy have been both flattened and reordered by members of the Montreal Hip-Hop community, whose multilingual lyrics insist: (1) that while French is the lingua franca, it is a much more inclusive category which includes ‘Bad French,’ regional and class dialects, and European French; and (2) that all languages spoken by community members are valuable as linguistic resources for creativity and communication with multiple audiences. We draw from a database which includes interviews with and lyrics from rappers of Haitian, Latin-American, African-American and Québécois origin.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1467-9841.2008.00393.x
Keywords: Order of indexicalities; Quebec language policy; multilingual code-switching; normative tradition (French); rap lyrics; urban youth culture

"Pour connecter avec le peeps": Québéquicité and the Quebec Hip-Hop Community - Sarkar, Mela; Low, Bronwen; Winer, Lise (Identity and Second Language Learning: Culture, Inquiry, and Dialogic Activity in Educational Contexts, 2006)

Translanguaging in the Multilingual Montreal Hip-Hop Community: Everyday Poetics as Counter to the Myths of the Monolingual Classroom - Low, Bronwen; Sarkar, Mela (Heteroglossia as Practice and Pedagogy, 2014)
This chapter explores the possibilities multilingual hip-hop offers for language instruction within multiethnic classrooms in Montreal shaped by multiple discursive practices. The authors review current research on multilingualism and teaching and propose strategies for overcoming the French prescriptivist monolingual mindset in education in Quebec. They also turn to poetics, and in particular the literary theory of Edouard Glissant (Caribbean discourse, 1989; Poetics of relation, 1997) and the Martinican school of Créolité, offering possibilities for rethinking relationships between oral and written, vernacular and standard language forms and for igniting language teachers’ pedagogic imaginations.
Keywords: Creolization; Hip-hop; Oraliture; Popular culture

"Still Reppin' Por Mi Gente": The Transformative Power of Language Mixing in Quebec Hip Hop - Sarkar, Mela (Global Linguistics: Hip Hop Cultures, Youth Identities, and the Politics of Language, 2008)

Multilingual code-switching in Montreal Hip-Hop: Mayhem meets method, or, ‘Tout moune qui talk trash kiss mon black ass du nord’ - Sarkar, Mela; Winer, Lise; Sarkar, Kobir (ISB4: Proceedings of the 4th International Symposium on Bilingualism, 2005)